Postoperative Spine Infection: Diagnosis and Management. Issue 4 (December 2018) - Dowdell, James; Brochin, Robert; Kim, Jun; Overley, Samuel; Oren, Jonathan; Freedman, Brett; Cho, Samuel
Study Design: Review article. Objectives: A review of the literature on postoperative spinal infections, their diagnosis, and management. Methods: A systematic computerized Medline literature search was performed using PubMed, Cochrane Database of Systematic Reviews, and EMBASE. The electronic databases were searched for publication dates from the last 10 years. The searches were performed from Medical Subject Headings (MeSH) used by the National Library of Medicine. Specifically, MeSH terms "spine, " "infections, " "management, " and "diagnosis" were used. Results: Currently, the gold standard for diagnosis of postoperative spine infection is positive deep wound culture. Many of the current radiologic and laboratory tests can assist with the initial diagnosis and monitoring treatment response. Currently erythrocyte sedimentation rate, C-reactive protein, computed tomography scan, and magnetic resonance imaging with and without contrast are used in combination to establish diagnosis. Management of postoperative spine infection involves thorough surgical debridement and targeted antibiotic therapy. Conclusions: Postoperative spine infection is a not uncommon complication following surgery that may have devastating consequences for a patient's short- and long-term health. A high index of suspicion is needed to make an early diagnosis.